Comparative assessment of various methods of miscarriage treatment efficacy in multifetal pregnancy - Boiko, V. I.; Nikitina, I. M.; Sukhariev, A. B.; Kalashnyk, N. V. (Zaporozhye Medical Journal, 2018)
Aim. Comparative assessment of various methods of miscarriage treatment efficacy in multifetal pregnancy taking into account the cervical remodeling. Materials and Methods. 62 pregnant women with dichorionic twins were observed. The general, somatic, obstetric-gynecological anamnesis, the pregnancy and childbirth course and the state of newborns were studied. All women underwent transvaginal cervicometry throughout the pregnancy. The cervical length and the shape of internal cervical os were determined. Results. In women with uncomplicated pregnancy cervical length was shortened from 43.2 ± 3.9 mm to 38.2 ± 4.0 mm up to 20 weeks’ gestation, from 37.7 ± 4.1 mm to 30.2 ± 3.9 mm up to 30 weeks and to 21.1 ± 3.1 mm up to 37 weeks. In the period of 25–27 weeks V-shaped endocervical canal opening was observed in half of the women and remained until the end of gestation. Cervix shortening was most pronounced in patients with pregnancy threatening miscarriage, who received only tocolytic therapy. In the 2nd trimester V- or U-shaped endocervical canal opening was observed. At 34–36 weeks the length of cervix was significantly shorter than in uncomplicated pregnancy. The rate of cervical length shortening among pregnant women of the risk group, who were treated with a vaginal pessary, and women with uncomplicated pregnancy was similar. The cervical remodeling with a vaginal pessary was not significantly different from that in normal course of multifetal pregnancy before childbirth. In addition, there were no significant differences in the characteristics of delivery, the perinatal mortality indicators and the newborns state. Conclusions. In pregnant women with uncomplicated multifetal pregnancy cervical length shortening is observed as the gestational age increases. In pregnant women with pregnancy threatening miscarriage, who received tocolytic therapy, the cervix was the most shortened. V- and U-shaped endocervical canal changes were observed in the late gestation. Changes in the cervix after vaginal pessary placement are similar to those in uncomplicated pregnancy.